Effects of age and tree portion on chemical properties of Leucaena Leucocephala wood / Wan Mohd Nazri Wan Abd Rahman ...[et al.] - Wan Abd Rahman, Wan Mohd Nazri; Kasim, Jamaludin; Mohd Nawawi, Rudaini; Sudin, Rahim; Mohd Yunus, Nor Yuziah (Universiti Teknologi MARA Cawangan Pahang, 2008)
The chemical components of wood strongly influence the characteristics, properties and opportunities for use of wood as composite material. The data on the chemical composition of wood material is generally preferred and required for various processes and applications in the wood industry. The main objective of the study is to determine the basic chemical properties of Leucaena leucocephala from eight year-old and sixteen year-old trees. This study revealed that age shows no significant effect while tree portion significantly affect the cold water and hot water solubles. Alkali solubility also shows similar trend. Alcohol toluene soluble was significantly affected by age and tree portion. Effect of tree portion in ash content shows a significant difference between bottom and both middle and top portions. However, effect of age shows no significant difference with percentage of ash content. The lignin content shows a positive correlation with increasing age but correlated insignificantly with tree portion. The holocellulose content decreases significantly with age and positive increases with tree portion. Generally, eight year-old wood was found to be a suitable raw material to manufacture wood composite.